PERANCANGAN ALAT BANTU YANG ERGONOMI DENGAN SOFTWARE AUTOCAD UNTUK MENUNJANG PROSES PRODUKSI KERUPUK KULIT - Muhammad Farhan Ramadhan; Wahyudin Wahyudin; Billy Nugraha (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2022)
MSMEs have contributed to increase state revenue. This can be seen from the marketing of MSMEs products to abroad. One of them is the typical Karawang Farida skin crackers MSMEs located in Perumnas Permata Telukjambe Blok MC No. 36, Sukaluyu, Telukjambe Timur District, Karawang Regency. The problem that occurs at the MSMEs is the lack of supporting facilities in the production process carried out. The objectives in this study will produce a design of tools that are in accordance with the current problems. Research methods with the approach to design aids through the help of AutoCAD software. So, the right type of conveyor is used is a conveyor belt because with this conveyor skin crackers whose oil has been able to immediately walk to the final shelter. Oil that is accommodated will be flowed through a pipe that will be flowed back to the frying pan so that no oil is wasted after frying crackers. As a conclusion in this writing, the design of the tools needed by the MSMEs owner. So it is hoped that the design of this aids can increase work productivity during the production process.